Giải hệ phương trình sau $\begin{cases} 4x^2 + y^2 + 4xy = 4 \\ x^2 + y^2 – 2(xy + 8) = 0 \\\end{cases}$

Question

Giải hệ phương trình sau
$\begin{cases} 4x^2 + y^2 + 4xy = 4 \\ x^2 + y^2 – 2(xy + 8) = 0 \\\end{cases}$

in progress 0
Gerda 5 months 2021-05-06T11:43:42+00:00 1 Answers 3 views 0

Answers ( )

    0
    2021-05-06T11:44:58+00:00

    Đáp án: $(x;y)∈\{(2;-2);(\dfrac{2}{3};\dfrac{-10}{3});(\dfrac{-2}{3};\dfrac{10}{3});(-2;2)\}$

     

    Giải thích các bước giải:

    $\begin{cases}4x^2+y^2+4xy=4\\x^2+y^2-2(xy+8)=0\end{cases}⇔\begin{cases}(2x+y)^2=4\\(x-y)^2-16=0\end{cases}⇔\begin{cases}2x+y=±2\\x-y=±4\end{cases}$

    Xảy ra $4$ hệ sau:

    $1)\begin{cases}2x+y=2\\x-y=4\end{cases}⇔\begin{cases}(2x+y)+(x-y)=2+4\\x-y=4\end{cases}⇔\begin{cases}3x=6\\y=x-4\end{cases}$

    $⇔\begin{cases}x=2\\y=x-4\end{cases}⇔\begin{cases}x=2\\y=-2\end{cases}$

    $2)\begin{cases}2x+y=-2\\x-y=4\end{cases}⇔\begin{cases}(2x+y)+(x-y)=-2+4\\x-y=4\end{cases}⇔\begin{cases}3x=2\\y=x-4\end{cases}$

    $⇔\begin{cases}x=\dfrac{2}{3}\\y=x-4\end{cases}⇔\begin{cases}x=\dfrac{2}{3}\\y=\dfrac{-10}{3}\end{cases}$

    $3)\begin{cases}2x+y=2\\x-y=-4\end{cases}⇔\begin{cases}(2x+y)+(x-y)=2-4\\x-y=-4\end{cases}⇔\begin{cases}3x=-2\\y=x+4\end{cases}$

    $⇔\begin{cases}x=\dfrac{-2}{3}\\y=x+4\end{cases}⇔\begin{cases}x=\dfrac{-2}{3}\\y=\dfrac{10}{3}\end{cases}$

    $4)\begin{cases}2x+y=-2\\x-y=-4\end{cases}⇔\begin{cases}(2x+y)+(x-y)=-2-4\\x-y=-4\end{cases}⇔\begin{cases}3x=-6\\y=x+4\end{cases}$

    $⇔\begin{cases}x=-2\\y=x+4\end{cases}⇔\begin{cases}x=-2\\y=2\end{cases}$

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )